AL-QURAN DAN PEMANFAATAN PERMAINAN EDUKATIF PADA ANAK USIA DINI - Atik Wartini Muhammad Askar (Fakultas Ilmu Agama Islam Universitas Indragiri, 2015)
This research is based on a literature review, in this study the theme was related to the Koran and utilization of educational games for children early age, in this paper, there are three first questions how the Koran speaks of utilization Educational games, both what just utilization educational games, and any third party utilization educational games, with the method of content analysis it will be produced first know the Koran speaks utilization of educational games, second, meaning educational games, and third to know what can be utilized in educational games.